Prevalence and factors associated with neonatal sepsis among hospitalized newborns at Ruvuma, southern Tanzania - Mekitrida L. Kiwone; Nikolaus S. Chotta; Daniel Byamungu; Fabian P. Mghanga (Health and Social Sciences Research Institute - South Sudan (HSSRI-SS), 2020)
Introduction: Neonatal sepsis is one of the most common causes of neonatal morbidity and mortality in developing countries. Objective: This study aimed to determine the prevalence and factors associated with neonatal sepsis among hospitalized new-borns at Ruvuma, southern Tanzania. Methods: A facility-based retrospective study was conducted at Songea Regional Referral hospital in Ruvuma, during August-October, 2018. A standardized questionnaire was used to collect demographic, obstetric and clinical information from medical case files of patients. Neonatal sepsis was diagnosed clinically. Data were analysed using SPSS version 24.0. Chi square test was used to assess relationship between outcome and exposure variables. Multivariate logistic regression was used to measure association after controlling for confounders, and P-values of <0.05 were statistically significant. Results: Medical case files of 263 neonates were reviewed. Of these, 131(49.8%) had sepsis. Factors associated with neonatal sepsis were prematurity (AOR=2.2; 95%CI. 1.3 - 3.6, p=0.002), age of more than a week (AOR=2.2; 95%CI. 1.0 - 4.6, p=0.04), intravenous cannulation after birth (AOR=6.3; 95%CI. 2.1 - 19.0, p=0.002), and resuscitation with nasal oxygen prongs (AOR=1.7; 95%CI. 1.1 - 2.9, p=0.02). Conclusions: Neonatal sepsis is relatively common among neonates in Ruvuma and is associated with maternal and health services related factors. The findings underscore the importance of routine assessment and close monitoring of neonates.